Fatal reactivation of hepatitis B virus infection in a patient with adult T‐cell leukemia–lymphoma receiving the anti‐CC chemokine receptor 4 antibody mogamulizumab. Issue 13 (15th April 2015) - Ifuku, Hideki; Kusumoto, Shigeru; Tanaka, Yasuhito; Totani, Haruhito; Ishida, Takashi; Okada, Masaya; Murakami, Shuko; Mizokami, Masashi; Ueda, Ryuzo; Iida, Shinsuke
Abstract : We report an adult T‐cell leukemia–lymphoma (ATL) patient suffering from fatal reactivation of hepatitis B virus (HBV) infection after treatment with the anti‐CC chemokine receptor 4 (CCR4) monoclonal antibody, mogamulizumab. HBV reactivation occurred without liver damage in this hepatitis B surface antigen (HBsAg) negative patient, who was seropositive for antibodies against the viral core and surface antigens at baseline, after two cycles of CHOP regimen (cyclophosphamide, doxorubicin, vincristine and prednisolone) followed by six cycles of THP‐COP regimen (cyclophosphamide, pirarubicin, vincristine and prednisolone). Unexpectedly, mogamulizumab monotherapy for relapsed CCR4 positive ATL induced sudden and fatal liver failure due to HBV reactivation, despite antiviral prophylaxis with entecavir. This clinical course may not only offer important suggestions to prevent critical HBV reactivation in HBsAg positive cancer patients who receive immune‐enhancing drugs such as anti‐CCR4 antibody, but also provide a clue to understanding the pathogenesis of HBV reactivation following systemic chemotherapy.